Urgency of Proper E-Waste Management Plan in Nepal: An Overview - Giri, Jyoti; Adhikari, Rameshwar (Nepal Journal of Science and Technology, 2020)
Electrical and electronic gadgets (or E-gadgets) have become indispensable components of our daily life these days. As today’s electrical and electronic devices become tomorrow’s waste, the potential hazards of these materials in an open environment are significant, as they can contaminate soil, drinking water, air and thus directly affecting human health and surrounding biota. With time, the random disposal of these wastes may lead to a disastrous situation. Although Nepal is one of the least developed countries, also in terms of electrical and electronic equipment, we are importing the high-tech E-gadgets from the developed nations and using them without a proper vision for their after-use management and their impacts on socio-economic values as well as health and environment. It has become an urgent need of the hour to address E-waste challenges taking into consideration the best suited international policies and practices.